2002
DOI: 10.1542/peds.109.6.1061
|View full text |Cite
|
Sign up to set email alerts
|

Natural History and Familial Relationships of Infant Spilling to 9 Years of Age

Abstract: Spilling in infancy is very common, but the majority of children settle by 13 to 14 months of age. However, those with frequent spilling (>90 days) are more likely to have GER symptoms at 9 years of age. In addition, a maternal history of GER was significantly related both to infant spilling and to GER at 9 years, suggesting that a genetic component may be involved. Physicians should consider studying children with a history of frequent infant spilling to determine whether this group is at increased risk for G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
155
0
13

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(174 citation statements)
references
References 31 publications
6
155
0
13
Order By: Relevance
“…This prevalence is similar to the one described in the literature, regardless of the diagnostic criteria used, 4,5,[17][18][19][20] suggesting that the use of the Rome Criteria may be useful in identifying infants who do not meet the criteria for IR and who therefore have to be more carefully evaluated.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This prevalence is similar to the one described in the literature, regardless of the diagnostic criteria used, 4,5,[17][18][19][20] suggesting that the use of the Rome Criteria may be useful in identifying infants who do not meet the criteria for IR and who therefore have to be more carefully evaluated.…”
Section: Discussionsupporting
confidence: 82%
“…4,5,[18][19][20] Prevalence decreases with age, characterizing the benign course of the disorder, contrary to GERD, where prevalence increases with age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Less is known about the normal physiology of GER in infants and children, but regurgitation or spitting up, as the most visible symptom, is reported to occur daily in 50% of all infants. 7,8 In both infants and children, reflux can also be associated with vomiting, defined as a forceful expulsion of gastric contents via a coordinated autonomic and voluntary motor response. Regurgitation and vomiting can be further differentiated from rumination, in which recently ingested food is effortlessly regurgitated into the mouth, masticated, and reswallowed.…”
Section: Introductionmentioning
confidence: 99%
“…89,90 A randomized trial found no benefit to treatment of symptoms attributed to gastroesophageal reflux disease in infants but did find that medication increased the risk of lower respiratory tract infections. 91 Yet gastroesophageal reflux disease diagnoses and treatments with medication for infants are common and increasing.…”
Section: Gastroesophageal Refluxmentioning
confidence: 99%